Classical Islamic Fatwa Framework in Mu'amalat for Islamic Banking Institutions - Salisu, Auwal; Mohamed Saniff, Shereeza; Akram Hassan, Shahir (KnE Social Sciences, 2023)
(Al-Falah Wa Al-Salah) and to eliminate economic injustice and unfairness. One of the ways to achieve this aim is through an effective operation of Islamic banking institutions according to Islamic Jurisprudence. Thus, existing literatures on Islamic banking institutions seems to suggest the inadequacy and the failure to comprehensively settle many aspects of economics and financial problems of the world, especially the Muslims. In Mu’amalat, a Muslim must ensure that the buying and selling transaction are set according to religious guidelines, so that one can avoid falling into forbidden transactions and unlawful forms of earning. In order to achieve the objectives of this study, through documentary review of existing literatures, narratives, as well as conceptual approach of analysis are used to present a sound legal theory of Fatwa under Islamic Jurisprudence. At the end, this paper proves that the use of classical Islamic Fatwa indicates that it provides one of the best forms of eliminating economic injustice and unfairness that sufficiently provides for the endeavours toward sustainable human wellbeing. Other financial institutions might use and adopt classical Islamic Fatwa in Mu’amalat aspect for better and smooth take-up of other types of Islamic financial institutions regarding Fatwa issuance. Keywords: classical Islamic Fatwa, banking institutions, Mu’amalat, sustainable, human well-being